Genotyping ITS and matK regions of Hedera nepalensis K. Koch in Vietnam - Thi Hong Nhung, Pham; Hanh Nguyen, Do; Thi Yen, Bui; Thi Le Hang, Do; Thi Thom, Vu; Doan Long, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3, 2020)
This study develops procedures for cloning ITS and matK genes on six specimens in order to exploit and conserve the genetic resources of H. nepalensis and evaluate its genetic diversity based on molecular markers. The study methods include DNA extraction from dried leaf samples, amplification of ITS and matK regions using PCR, sequencing and comparing with the sequences on Genbank. The study results include a successfully-established process of cloning ITS and matK genes; successful amplification and sequencing of the ITS and matK regions. The results also show that four samples (N1-N4) were 100% homologous to H. nepalensis and H1and H2 samples were 100% homologous to H. helix . The results provide data and tools for further studies of exploitation and development of the H. nepalensis K. Koch genetic resources in Vietnam. Keywords ITS, matK, Hedera nepalensis K. Koch, PCR References [1] V.V. Chi. Dictionary of Vietnamese Medicinal Plants, Publ. House Medicine, Ho Chi Minh City, 2012 (in Vietnamese). [2] D.H. Bich, D.Q. Cuong, B.X. Chuong, N. Thuong, D. T. Dam. The medicinal plants and animals in Vietnam, Hanoi Sci. Technol. Publ. House Hanoi, 2006 (in Vietnamese). [3] A. Sadat, M. Alam, A. Rauf, W. Ullah, Biological screening of ethyl acetate extract of Hedera nepalensis stem, Afr J Pharm Pharmacol, 6 (2012) 2934-2937. https://doi.org/10.5897/AJPP12.828. [4] T. Li, H. Pan, Y. Feng, H. Li, Y. Zhao, Bioactivity-guided isolation of anticancer constituents from Hedera nepalensis K. Koch, S Afr J Bot, 100 (2015) 87-93. https://doi.org/10.1016/j.sajb.2015.05.011. [5] L. Jafri, S. Saleem, N. Ullah, B. Mirza, In vitro assessment of antioxidant potential and determination of polyphenolic compounds of Hedera nepalensis K. Koch, Arab J Chem, 10 (2017) 3699-3706. https://doi.org/10.1016/j.arabjc.2014.05.002. [6] S. Saleem, L. Jafri, I. ul Haq, L.C. Chang, D. Calderwood, B.D. Green, B. Mirza, Plants Fagonia cretica L. and Hedera nepalensis K. Koch contain natural compounds with potent dipeptidyl peptidase-4 (DPP-4) inhibitory activity, J Ethnopharmacol, 156 (2014) 26-32. https://doi.org/10.1016/j.jep.2014.08.017. [7] W.J. Hashmi, H. Ismail, F. Mehmood, B. Mirza, Neuroprotective, antidiabetic and antioxidant effect of Hedera nepalensis and lupeol against STZ+ AlCl 3 induced rats model, DARU, 26 (2018) 179-190. https://doi.org/10.1007/s40199-018-0223-3. [8] H. Ismail, A. Rasheed, I.-u. Haq, L. Jafri, N. Ullah, E. Dilshad, M. Sajid, B. Mirza, Five indigenous plants of Pakistan with Antinociceptive, anti-inflammatory, antidepressant, and anticoagulant properties in Sprague Dawley rats, Evid Based Complement Alternat Med, 2017 (2017). https://doi.org/10.1155/2017/7849501 [9] N.D. Thanh. DNA marker techniques in study and selection of plant. Journal of Biology. 36 (2014) 265-294 (in Vietnamese). https://doi.org/10.15625/0866-7160/v36n3.5974. [10] P.Z. Goldstein, R. DeSalle, Review and interpretation of trends in DNA barcoding, Front Ecol Evol, 7 (2019) 302. https://doi.org/10.3389/fevo.2019.00302. [11] S. Abugalieva, L. Volkova, Y. Genievskaya, A. Ivaschenko, Y. Kotukhov, G. Sakauova, Y. Turuspekov, Taxonomic assessment of Allium species from Kazakhstan based on ITS and matK markers, BMC plant biol, 17 (2017) 258. https://doi.org/10.1186/s12870-017-1194-0. [12] R.M. Bhagwat, B.B. Dholakia, N.Y. Kadoo, M. Balasundaran, V.S. Gupta, Two new potential barcodes to discriminate Dalbergia species, PloS one, 10 (2015) e0142965. https://doi.org/10.1371/journal.pone.0142965 [13] D. Grivet, R. Petit, Phylogeography of the common ivy (Hedera sp.) in Europe: genetic differentiation through space and time, Mol Ecol, 11 (2002) 1351-1362. https://doi.org/10.1046/j.1365294x.2002.01522.x. [14] R. Li, J. Wen, Phylogeny and biogeography of Dendropanax (Araliaceae), an amphi-Pacific disjunct genus between tropical/subtropical Asia and the Neotropics, Syst Bot, 38 (2013) 536-551. https://doi.org/10.1600/036364413X666606. [15] Y. Sun, D. Skinner, G. Liang, S. Hulbert, Phylogenetic analysis of Sorghum and related taxa using internal transcribed spacers of nuclear ribosomal DNA, ‎Theor Appl Genet, 89 (1994) 26-32. https://doi.org/10.1007/BF00226978 [16] P. Cuénoud, V. Savolainen, L.W. Chatrou, M. Powell, R.J. Grayer, M.W. Chase, Molecular phylogenetics of Caryophyllales based on nuclear 18S rDNA and plastid rbcL, atpB, and matK DNA sequences, Am J Bot, 89 (2002) 132-144. https://doi.org/10.3732/ajb.89.1.132. [17] D. Bošeľová, J. Žiarovská, L. Hlavačková, K. Ražná, M. Bežo, Comparative analysis of different methods of Hedera helix DNA extraction and molecular evidence of the functionality in PCR Acta fytotechn zootechn, 19 (2016) 144-149. https://doi.org/10.15414/afz.2016.19.04.144-149. [18] D.D. Long, Comparative analysis of different DNA extraction methods and preliminary analysis of genetic diversity of Hedera nepalensis K. Koch. in Vietnam based on GBSSI marker, VNU Journal of Science: Medical and Pharmaceutical Sciences, 35 (2019) 88-95 (in Vietnamese). https://doi.org/10.25073/2588-1132/vnumps.4165 [19] J.H. Cota-Sánchez, K. Remarchuk, K. Ubayasena, Ready-to-use DNA extracted with a CTAB method adapted for herbarium specimens and mucilaginous plant tissue, Plant Mol Biol Rep, 24 (2006)161. https://doi.org/10.1007/BF02914055. [20] S. Xu, D. Li, J. Li, X. Xiang, W. Jin, W. Huang, X. Jin, L. Huang, Evaluation of the DNA barcodes in Dendrobium (Orchidaceae) from mainland Asia, PloS one, 10 (2015) e0115168. https://doi.org/10.1371/journal.pone.0115168. [21] P. Vargas, H.A. McAllister, C. Morton, S.L. Jury, M.J. Wilkinson, Polyploid speciation in Hedera (Araliaceae): Phylogenetic and biogeographic insights based on chromosome counts and ITS sequences, Pl Syst Evol, 219 (1999) 165-179. https://doi.org/10.1007/BF00985577 [22] X. Lei, Y.W. Wang, S.Y. Guan, L.J. Xie, L. Xin, C.Y. Sun, Prospects and problems for identification of poisonous plants in China using DNA barcodes, Biomed Environ Sci, 27 (2014) 794-806. https://doi.org/10.3967/bes2014.115. [23] H. Sun, W. McLewin, M.F. Fay, Molecular phylogeny of Helleborus (Ranunculaceae), with an emphasis on the East Asian‐Mediterranean disjunction, Taxon, 50 (2001) 1001-1018. https://doi.org/10.2307/1224717.